HUBUNGAN MUTU PELAYANAN TENAGA KESEHATAN DENGAN KEPUASAN PASIEN RAWAT JALAN RUANG POLI UMUM DI PUSKESMAS SEI AGUL MEDAN - Muhammad A. Kurnia; Rosalina Gultom; Masryna Siagian; Ermi Girsang (Jurnal Kesmas Prima Indonesia, 2021)
Indonesian people at this time need quality health services that can be seen based on the level of patient satisfaction in Indonesia that shows the patient's satisfaction rate of 42.8%. In Sei Agul Puskesmas there are outpatient who expressed dissatisfaction as much as 49 people (51.6%). This research aims to determine the relationship quality of healthcare professionals with the satisfaction of a general Poly chamber patient in the health center of Sei Agul. The type of research used in this study is an analytical survey using the Cross-Sectional approach. The number of samples in this study was 95 outpatient. The sampling technique used is Purposive Sampling. Data retrieval using questionnaire measuring instrument. Analysis of data conducted in the analysis of Univariate and bivariate (test Chi- Square) with a degree of significance p Value = 0.05. The results showed that the reliability with the value p value = 0.006 (P Value < 0.05), responsiveness with the value p value = 0.002 (p value < 0.05), the guarantee with the value P value = 0.003 (P Value < 0.05), empathy with the value p value = 0.386 (p value > 0.05), and physical evidence with the value p value = 0.019 (p Value < 0,05). The conclusion of this research is there is a relationship of reliability with patient satisfaction, there is a response of responsiveness to patient satisfaction, there is a guarantee relationship with patient satisfaction, no empathy relationship with patient satisfaction and there is a relationship of physical evidence with patient satisfaction.